Pengaruh Manajemen Kelas terhadap Disiplin Belajar Siswa Kelas Xl Di SMA Negeri 1 Siantar Narumonda Tahun Ajaran 2025/2026” - Anjelina Putri Manurung; Binur Panjaitan; Tahoma Fetriany Siburian; Endang Juliati Manullang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
his study aims to determine the effect of classroom management on the learning discipline of eleventh-grade students at SMA Negeri 1 Siantar Narumonda in the 2025/2026 academic year. The method used in this research is an inferential quantitative method. The population of this study consisted of all eleventh-grade students totaling 279 students, while the research sample consisted of 70 students selected using a random sampling technique. The data collection technique used a closed questionnaire that had been tested for validity and reliability, consisting of 36 items for the classroom management variable and 36 items for the learning discipline variable. The results of the data analysis show that the data are normally distributed with an Asymp. Sig. (2-tailed) value of 0.200 > 0.05 and have a linear relationship with a deviation of linearity value of 0.065 > 0.05. The correlation test results obtained rxy = 0.676 > rtable = 0.235, indicating a positive relationship between classroom management and students’ learning discipline. The significance test shows that tcount = 7.557 > ttable = 1.995. The regression equation obtained is Ŷ = 53.556 + 0.594X with a coefficient of determination of 45.6%. The F-test results show Fcount = 57.101 > Ftable = 4.00. Thus, H0 is rejected and Ha is accepted. Based on these results, it can be concluded that classroom management has a positive and significant effect on the learning discipline of students at SMA Negeri 1 Siantar Narumonda in the 2025/2026 academic year.